Adolescent Weight Status and Self-Reported School Performance in South Korea. (14th November 2011) - Do, Young Kyung; Finkelstein, Eric Andrew
Abstract : Using a nationally representative sample of 142 783 middle school (13–15 years old) and high school (16–18 years old) students in South Korea, this study examined whether (1) overweight and obesity are more likely to be associated with lower self-reported school performance; (2) overweight and obese students are more likely to enrol in a vocational high school as opposed to a general high school; (3) the association between obesity and poorer self-reported school performance is mediated through body image stress and health status. We found that excess weight was negatively associated with self-reported school performance among middle and general high school students, and that obese students had a higher probability of being enrolled in a vocational over a general high school. We did not find strong evidence on the mediating role of body image stress and health status.